The incentive effects of monetary policy on fiscal policy behaviour - Joost Röttger; Rafael Gerke (Deutsche Bundesbank, 2021)
How do prolonged low-interest-rate episodes affect fiscal discipline? This paper investigates this question by using a quantitative model with endogenous public debt management and sovereign default. Following a persistent interest rate reduction, sovereign risk and government bond yields decline. An impatient fiscal policy maker responds to improved financing conditions by relaxing its policy stance and accumulating more debt. Due to the increased debt burden, a subsequent interest rate reversal can put substantial pressure on the public budget, raising the likelihood of default. The longer the interest rate cut is expected to last, the more pronounced the fiscal response will be.
Keywords: E52; E62; H63; 330; Public Debt; Sovereign Risk; Low-Interest-Rate Policies